Joint Communication and Navigation From LEO Multi-Beam Satellite - Alejandro Gonzalez-Garrido; Jorge Querol; Henk Wymeersch; Symeon Chatzinotas (IEEE Open Journal of the Communications Society)
This paper investigates an innovative approach to enable Joint Communication and Positioning (JCAP) in 5G Non-Terrestrial Networks (NTN) using Low Earth Orbit (LEO) multi-beam satellite systems. The integration of communication and navigation services is achieved by aggregating a Direct-Sequence Spread Spectrum (DSSS) as a navigation signal with a 5G Orthogonal Frequency-Division Multiplexing (OFDM) waveform for communication services. Two models are proposed for resource allocation and signal aggregation, referred to as the shared beam model, where communication and navigation signals are aggregated prior to Digital Beamforming (DBF) within the same beam; and the independent beam model, which employs separate beams for communication and navigation, with the navigation beam designed to be significantly wider than the communication beams, resulting in overlap between the two. The performance of these models is assessed using as Key Performance Indicators (KPI) the Cramer-Rao Lower Bound (CRLB) for range estimation used in navigation and the spectral efficiency for the broadband service. The study formulates and addresses a multi-objective optimization problem to derive the Pareto front, highlighting the trade-off between communication and navigation performance. Extensive simulations demonstrate the efficacy of the proposed models in terms of spectral efficiency and accuracy in range estimation, and results have been compared with those obtained from the current 5G positioning system. The models have been evaluated in two distinct scenarios: one without frequency reuse between beams and another incorporating a three-color frequency reuse scheme. The results indicate that the independent beams model outperforms the shared beams model by reducing inter-beam interference in both scenarios. The proposed solution maintains backward compatibility with existing 5G NTN, facilitating uninterrupted positioning and communication services in GNSS-denied environments. Furthermore, the combination of DSSS and OFDM enhances the reliability of the data service by utilizing the DSSS sequence as a digital signature for the waveform. This work establishes a foundation for robust and efficient JCAP implementations, addressing challenges related to multi-beam interference and resource optimization.